The rapid response and high sensitivity of a ruthenium-doped copper ferrite thin film (Ru–CuFe2O4) sensor. Issue 23 (3rd April 2020) - Manikandan, V.; Mirzaei, Ali; Sikarwar, S.; Yadav, B. C.; Vigneselvan, S.; Vanitha, A.; Chandrasekaran, J.
Abstract : A sensor displaying a rapid response and high sensitivity was developed by following a simple route. Abstract : A sensor displaying a rapid response and high sensitivity was developed by following a simple route. Ionic defects in this sensor were explored using X-ray diffraction analysis. In general, such defects arise from a mismatch of ionic radii, which actually improves the sensing performance. SEM and TEM images of the currently produced particles demonstrated negligible agglomeration, which greatly enhanced the flow of water molecules through the particles. The current sensor showed a rapid response to changes in humidity. Its sensing performance was classified into three different ranges of humidity. Of these humidity ranges, the sensor showed the highest sensitivity (8.84 MΩ per %RH) at low relative humidity (10–20% RH). Furthermore, the sensitivity fall off as the RH was increased from 20 to 99%. The sensor showed a rapid response time of 20 s. Also, the sensor showed 92.98% reproducibility and few effects of aging.